Producing Kombucha Beads by Spherification: Effect of Alginate Concentration on Release Behavior and Physical Characteristics - Cakrawati, Dewi; Tresuwan, Khemapas; Rahayu, Dwi Lestari; Sulastri, Afianti; Handayani, Mustika Nuramalia; Sugiarti, Yatti; Tanesha, Josephine (Indonesian Food Science and Technology Journal, 2025)
Abstract— The consumption of kombucha has been increasing in recent years due to its health benefits. However, its strong and distinctive flavor can be a limiting factor for consumer acceptance. Therefore, producing kombucha beads through spherification provides an alternative method of consuming kombucha. This study investigated the effect of sodium alginate (SA) concentration on the release of total phenolic content, reducing sugar, and antioxidant capacity from kombucha beads. Additionally, the stability of kombucha beads in simulated gastric juice was investigated in terms of viable bacteria.  The microstructure of kombucha beads was investigated using a scanning electron microscope (SEM). The result showed that kombucha beads produced tear-shaped beads. Increasing the concentration of sodium alginate led to an increase in the size and hardness of the kombucha beads (P < 0.05). However, increasing the concentration of sodium alginate did not affect the release of total phenolic content, reducing sugar and antioxidant capacity (P ≥ 0.05). Interestingly, 1% SA-kombucha beads had the highest viability of bacteria (P < 0.05) after low pH simulation compared to 2% to 5% SA-kombucha beads. SEM analysis revealed that kombucha beads had cavities and deposits of NaCl at 2% and higher concentrations of sodium alginate. While the FTIR spectra showed that no new peaks were generated in the kombucha beads, stretching peaks were observed at 3000-3500 cm-1. This study highlighted the potential of alginate beads for encapsulating polyphenolic compounds as an innovative approach for food applications. Further study is needed to understand the release behavior of probiotic microorganisms in kombucha during digestion.